Rethinking the Role of Circular Economy in Socially Sustainable Organizations Case: Ekomaa Recycling Store - Viljakainen, Kati; Kurkinen, Marika (European Journal of Sustainable Development, 2025)
Studies of the circular economy are often approached from the perspective of the economic and environmental impact. Using the case study of Ekomaa Recycling Store in Kouvola, Finland, this study examines the intersection of all four dimensions of sustainability, highlighting the social dimensions. The comprehensive sustainability framework is recognized as a key component of strategic decision-making, particularly in the circular economy context In February 2025, semi-structured interviews (6) were conducted with stakeholders, including the organization’s operational staff, managers, and strategic planners. The analysis is framed using four dimensions of sustainability and the United Nations Sustainable Development Goals (SDGs). Our findings indicate that Ekomaa’s impact extends beyond social sustainability, reinforcing the economic and environmental aspects of the circular economy. The workplace acts as a transformative environment where employees internalize sustainable practices. However, strategically incorporating sustainability could improve stakeholder engagement, resource distribution, and long-term adjustment. This study highlights Ekomaa as a best practice for integrating circular economy practices with social sustainability principles. It emphasizes the need for stronger sustainability strategies that foster participatory work cultures, behavioral transformation, and knowledge sharing. The results reveal that organizations that engage in circular economy initiatives can enhance social sustainability by embedding sustainability principles into their decision-making processes. Key Words: Sustainable Development, Circular Economy, Social Sustainability